INOVASI KURIKULUM BERBASIS BUDAYA LOKAL DI SDIT AL – WATHONIYAH PAJAGALAN SUMENEP - Tita Tanjung Sari; Ratna Novita Punggeti (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Abstract: Culture-based curriculum innovation in the Al-Wathoniyah Integrated Islamic Elementary School (SDITA) Sumenep includes several objectives, objectives, learning materials, media and infrastructure, learning strategies, learning processes, and evaluation or assessment. The goal of cultural-based curriculum innovation at SDITA is that religiosity, mutual respect, and positive competitive. Teaching materials are adapted to the 2013 revised 2018 curriculum with the development of teaching materials tailored to each grade level and student characteristics. Innovation in learning media is realized in the form of the SAC (Student Advisory Center) room. The learning methods applied at SDITA are three main methods. First, love by giving an example by instilling good values ​​in children. Second, mother tongue, namely the language of affection for children, because SDITA is a parent partner in educating children. Third, joint learning is to utilize the local environment and culture as the widest and most comprehensive laboratory that is the main source of children's learning. And evaluation in every learning is monitored and communicated well with parents as a form of Parenting education. Which is that SDITA applies that the school is a partner of parents in educating and teaching students. Learning evaluation is not only measured through tests but also focuses more on student learning experiences. Keywords: Curriculum Innovation, Local Culture. Abstrak : Inovasi kurikulum berbasis budaya di Sekolah Dasar Islam Terpadu Al – Wathoniyah (SDITA) Sumenep mencakup beberapa yakni tujuan yang ingin dicapai, materi belajar, media dan sarana prasana, strategi pembelajaran, proses pembelajaran, serta evaluasi atau penilaian. Tujuan inovasi kurikulum berbasis budaya di SDITA agar religiusitas, saling menghormati, dan kompetitif positif. Materi ajar disesuaikan dengan kurikulum 2013 revisi 2018 dengan pengembangan materi ajar disesuaikan dengan setiap jenjang kelas dan karakteristik siswa. Inovasi dalam media pembalajaran diwujudkan berupa ruang SAC (Student Advisory Center). Metode pembelajaran yang diterapkan di SDITA adalah tiga metode utama. Pertama, cinta dengan memberikan keteladanan dengan menanamkan nilai-nilai kebaikan pada anak. Kedua, bahasa ibu yakni dengan bahasa kasih saying pada anak, sebab SDITA adalah mitra orang tua dalam mendidik anak. Ketiga, belajar bersama yaitu memanfaatkan lingkungan dan budaya setempat seabagai laboratorium terluas dan terlengkap yang menjadi sumber utama belajar anak. Dan Evaluasi dalam setiap pembelajaran dipantau dan dikomunikasikan dengan baik dengan orang tua siswa sebagai salah satu bentuk Parenting education. Yang bahwasanya SDITA menerapkan bahwa sekolah adalah partner orang tua dalam mendidik dan mengajar siswa. Evaluasi pembelajaran tidak hanya di ukur lewat tes namum juga lebih menitikberatkan pada pengalaman belajar siswa. Kata Kunci: Inovasi Kurikulum, Budaya Lokal.